Improving Teachers’ Ability to Develop Assessment Techniques and Instruments Through the Academic Supervision at SMA Negeri 2 Tanggul Academic Year 2021/2022 - Imam Suja'i (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
Based on the results of initial observations, teachers of SMA Negeri 2 Tanggul found some problems in the preparation of the curriculum assessment techniques and instruments. Their assessment test questions do not meet good learning outcomes assessment criteria. One solution to this problem is to optimize the supervision of the school principal. With the supervision of the school principal, teachers will be assisted in developing student learning assessment techniques seriously, and as best as possible. The research method used in this study was school action research, with a class X teacher as the research participant. The results showed that the teachers’ ability to prepare student learning assessment techniques has significantly increased under the supervision of the school principal. This research gained three significant cycles, i.e. the pre-, the first, and the second, to identify the results of the assessment scores (test questions) prepared by the subject teachers. Their ability to develop assessment tools based on the data in the pre-cycle is only 56.16% as the average value of the components of the implementation of the learning process indicator of success. Then in the first cycle, the average value of the components of the implementation of the learning process increased to 74.36% and in the second cycle increased to 85.03%. Implementing the school principal's academic supervision in fostering teachers’ ability to develop student learning outcomes assessment has contributed significantly to their preparation in learning achievement test questions. During this supervision, the principal coaches teachers to practice compiling test assessments until they understand and are proficient in making test assessment of student learning outcomes.